PENGARUH KETIDAK PASTIAN LINGKUNGAN TERHADAP KARAKTERISTIK SISTEM IMPORMASI AKUNTANSI MANAJEMEN PADA BANK SYARIAH MANDIRI PEKANBARU - Dwika Lodia Putri; Jeni Wardi; Reni Farwitawati (PEKBIS, 2016)
This research goal is to determine the effect of environmental uncertainty on the characterustics of accounting information management system at Syariah Mandiri Bank Pekanbaru. The type of the research is associative research, the independent varable in this study is the uncertainty of the environment, the characteristics of management accounting information system as the dependent variable. Dimensional time this study was cross sectional population study of decision-making. The results of this study fit the hypothesis proposed is environmental uncertainty affects the characteristics of management accounting information systems.